2020
DOI: 10.1080/23802359.2020.1772692
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome of Onychostoma leptura and phylogenetic analysis of Onychostoma

Abstract: In this study, we first sequenced and characterized the complete mitochondrial genome of Onychostoma leptura. The complete mitochondrial genome was 16,601 bp in length and included 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNA), two ribosomal RNA genes (12S rRNA and 16S rRNA), and one non-coding control region (D-loop). The overall nucleotide composition was A: 31.31%, T: 23.89%, G:16.16%, and C: 28.64%, and the A þ T content (55.20%) was much higher than G þ C content (44.80%). The phylogenetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
(5 reference statements)
2
4
0
Order By: Relevance
“…The present study strongly supported that some species of Acrossocheilus, Onychostoma and F. brevifilis belong to the monophyletic group (Clade III), including A. monticola, A. yunnanensis, O. rarum, O. alticorpus and F. brevifilis. Interestingly, our results corroborate the previous finding that O. rarum is the sister group of O. alticorpus (Hoang et al 2015;Song et al 2018;Zhang et al 2018), but Zhai et al (2020) suggested that O. rarum appeared to be more closely related with O. barbatulum and O. barbatum. We suggested that the specimens of O. rarum (NC022869.1) were also misidentified.…”
Section: Molecular Phylogeny Of Onychostomasupporting
confidence: 92%
See 3 more Smart Citations
“…The present study strongly supported that some species of Acrossocheilus, Onychostoma and F. brevifilis belong to the monophyletic group (Clade III), including A. monticola, A. yunnanensis, O. rarum, O. alticorpus and F. brevifilis. Interestingly, our results corroborate the previous finding that O. rarum is the sister group of O. alticorpus (Hoang et al 2015;Song et al 2018;Zhang et al 2018), but Zhai et al (2020) suggested that O. rarum appeared to be more closely related with O. barbatulum and O. barbatum. We suggested that the specimens of O. rarum (NC022869.1) were also misidentified.…”
Section: Molecular Phylogeny Of Onychostomasupporting
confidence: 92%
“…Zhang et al (2018) also showed that the eight species of Onychostoma cluster into three separate lineages based on the whole mitochondrial genome sequence. However, similar research in Zhai et al (2020) only identified two lineages among nine species of Onychostoma with the same molecular markers. Interestingly, Zhang et al (2018) proposed that O. rarum (Lin, 1933) was the sister group of O. alticorpus (Oshima, 1920), but recently another study showed that O. rarum seems to be more closely related to O. barbatulum (Pellegrin, 1908) and O. barbatum (Lin, 1931) (Zhai et al 2020).…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“… 2018 ; Zhai et al. 2020 ). The initiation codon for all 13 PCGs was ATG except COI where it was GTG.…”
mentioning
confidence: 99%